IMPAIRMENT OF RENAL FUNCTION DETERMINED BY CREATININE AND CYSTATIN C LEVELS IN PATIENTS WITH HYPERTENSION AND FREQUENT EXTRASYSTOLES - Ivankova, A.V.; Kuzminova, N.V.; Lozinsky, S.E.; Knyazkova, I.I.; Kulchytska, O.M.; Shkarivsky, Yu.L.; Romanova, V.O. (World of Medicine and Biology, 2023)
156 patients with essential hypertension stage II were examined, among them 124 had frequent extrasystoles, and 32 did not have heart rhythm disorders. Another 30 practically healthy individuals entered the control group. All participants of the study underwent a complete clinical, laboratory, and instrumental examination, including the level of microalbuminuria, electrolytes, creatinine, and cystatin C with the calculation of the glomerular filtration rate. In patients with hypertension, the level of cystatin C was significantly higher compared to the control group (p